Kajian Transkultural: Naturalistik Dan Personalistik Terhadap Sehat Sakit Pada Masyarakat Jember - Aldo Apriyansah; Linda Febrianti; Iklima Najwa Billah; Abdul Aziz Azari (Poltekkes Kemenkes Tanjung Karang, 2024)
The community that adheres to the naturalistic concept assumes that a person suffers from illness due to the influence of the environment, food, lifestyle, and imbalance in the body. Meanwhile, the community that adheres to the personalistic concept assumes that the emergence of illness is caused by the intervention of an active agent that can be a non-human creature (ghost, spirit, ancestor, or evil spirit). This research aims to identify the perception of health and illness of the Jember community based on the theory of transcultural nursing in the scope of personalistic and naturalistic. This research is a descriptive study with a case study and a qualitative type of research. Data were obtained by conducting interviews with in-depth interview guide instruments. There were four main participants in this study and two additional participants. The steps in conducting research are preliminary studies, data collection, and conclusions. This research uses the Colaizzi method analysis technique. The study results show that the community believes that illness is caused by a person's biological condition, which is influenced by environmental conditions, adequate nutrition, lifestyle, body imbalance, and congenital diseases (naturalistic). The treatment method based on the naturalistic concept allows the community to get a cure for their illness by seeking treatment from modern medical health services, such as going to a doctor or buying medicine at a shop. People who understand and comprehend the meaning of illness and the causes of illness will determine their choice of treatment, whether naturalistic or personalistic.